Preliminary Investigation of Microbial Community in Wastewater and Surface Waters in Sri Lanka and the Philippines - Cruz, Andre Freire; Wijesekara, R. G. S.; Jinadasa, K. B. S. N.; Gonzales, Benjamin J.; Ohura, Takeshi; Guruge, Keerthi S. (Frontiers in Water, 2021)
In this study, the composition and richness of bacterial communities in treated and untreated wastewater from hospitals, commercial and non-commercial fish farming sites, sewage effluents, and surface waters which included seawater and fresh water in Sri Lanka and the Philippines were investigated through 16S rRNA gene amplicon sequence analysis. Firmicutes were found predominantly in Sri Lankan hospital wastewaters, while Cyanobacteria and Acidobacteria were typically detected in fish culture sites and the waste canal in Sri Lanka, respectively. The Shannon-Weaver index (SW) and number of Operational Taxonomic Units (OTUs) were higher in the Philippines than in Sri Lanka. The bacterial richness in the university noncommercial fish pond and sewage effluent displayed greater than that in hospital wastewaters. In addition, the bacterial richness was higher in the untreated wastewater compared to it in the treated wastewater in hospitals. These results indicate the differences among water types in terms of bacterial community, especially influenced by their source.